Preliminary Assessment of the Awareness Level of Radon and its Health Risks among High School Science Teachers and Health Workers in Nagongera, Tororo Uganda - Baniyo, Nahori; Biira, Saphina (East African Journal of Health and Science, 2024)
This study aims to evaluate the awareness levels regarding radon, its associated health risks, and potential mitigation strategies among high school science teachers and health workers in Nagongera Sub County, Tororo District, Uganda. Tororo District, known for its rich natural mineral resources, particularly around the Osukuru Hills, has attracted numerous industries. The combination of mineral-rich geography and substandard building structures may elevate health risks for residents due to radon exposure. An instrumental case study approach was adopted, utilizing a questionnaire designed to assess the awareness of radon-related health risks alongside demographic information such as occupation. The study surveyed 30 health workers and 30 high school science teachers, totalling 60 respondents. Findings revealed that fewer than half of the health workers (30%) and high school science teachers (40%) were aware of radon as a radioactive substance and its health implications. These results highlight the need for targeted efforts by relevant authorities to improve radon awareness among the general population in the district